Labels of Origin for Food: Local Development, Global Recognition 2011
DOI: 10.1079/9781845933524.0092
|View full text |Cite
|
Sign up to set email alerts
|

Public policies and geographical indications.

Abstract: This chapter sets out to widen the debate on geographical indications (GIs), situating protection policies in the EU in the broader context of the public policies with which they are more or less directly involved. First, after presenting the historical and geographical justifications behind GI protection policies, it will be seen that they relate to various wider public policies (market, agricultural, and rural development policies), with which they may be consistent or contradictory. Lastly, the chapter look… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…From the analysis, producers' willingness to pay for collective marketing for both products was KES 330 (USD 3.3) and KES 207 (USD 2.07) for mango and goat respectively (Table 7). Collective action is a major aspect for the success of GI protection (Barjolle and Sylvander, 2000; Reviron and Chappuis, 2011). By engaging in collective marketing, the producers present a joint product to the market, hence establishing exclusion and exclusion costs restricted to the production region, making it a private good.…”
Section: Resultsmentioning
confidence: 99%
“…From the analysis, producers' willingness to pay for collective marketing for both products was KES 330 (USD 3.3) and KES 207 (USD 2.07) for mango and goat respectively (Table 7). Collective action is a major aspect for the success of GI protection (Barjolle and Sylvander, 2000; Reviron and Chappuis, 2011). By engaging in collective marketing, the producers present a joint product to the market, hence establishing exclusion and exclusion costs restricted to the production region, making it a private good.…”
Section: Resultsmentioning
confidence: 99%
“…We derived relevant benefit categories from GI literature, e.g., vertical and horizontal integration, higher or better accepted quality standards, social learning processes (Sanz-Cañada and Macias-Vázquez, 2005; Giovannucci et al, 2009, 2010; Reviron and Chappuis, 2011; Coulet, 2012; Bagal et al, 2013; Barjolle, 2016), but we excluded benefits that would result from the actual use of the GI (e.g., price premiums, rural development benefits). In the action arena analysis and as explanatory variable of efforts, we also included risks linked to possible failures of the collective GI registration process (unsolvable conflicts, lack of information, unclear regulation) (Barjolle and Sylvander, 2000; Ilbery and Kneafsey, 2000; Giovannucci et al, 2009, 2010; Coulet, 2012; Rangnekar and Mukhopadhyay, 2016). However, we excluded post-registration risks that affect the GI use (e.g., inadequate consumer knowledge of the GI).…”
Section: Theoretical Framework and Methodsmentioning
confidence: 99%
“…They concluded that "a spatial planning approach, if successfully developed and enhanced, offers real value in the development of public policy" whereas "space and place are in fact relevant and significant in the development of public policy". Barjolle, Sylvander, & Thévenod-Mottet (2011) find that GI has been instrumental in EU common agricultural policy (CAP) and rural development. They argue, "Producers [of agricultural products] may be at an advantage or a disadvantage by virtue of their geographical location and their proximity to consumer centres".…”
Section: Role Of Spatial Information Within Policy-makingmentioning
confidence: 99%